2016
DOI: 10.1590/s1677-5538.ibju.2014.0500
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors leading to postoperative urethral stricture and bladder neck contracture following transurethral resection of prostate

Abstract: Purpose:To determine risk factors of postoperative urethral stricture (US) and vesical neck contracture (BNC) after transurethral resection of prostate (TURP) from perioperative parameters.Materials and Methods:373 patients underwent TURP in a Chinese center for lower urinary tract symptoms suggestive of benign prostatic obstruction (LUTS/BPO), with their perioperative and follow-up clinical data being collected. Univariate analyses were used to determine variables which had correlation with the incidence of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
2
34
0
4
Order By: Relevance
“…It is interesting to note that Tao et al [ 25 ] also recently reported that US is associated with slow resection rate. That study also found mucosal rupture of the urethra and continuous postoperative infection to be risk factors for US occurrence.…”
Section: Discussionmentioning
confidence: 98%
“…It is interesting to note that Tao et al [ 25 ] also recently reported that US is associated with slow resection rate. That study also found mucosal rupture of the urethra and continuous postoperative infection to be risk factors for US occurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Many risk factors, including small prostate volume, higher International Prostate Symptom Score storage scores, preoperative uncontrolled infection, unsuitable resectoscope, large resection loop, extensive resection of the bladder neck, long operative time and postoperative Foley insertion have been shown to be associated with the risk of BNC. 7,9 The most reported risk factor is small prostate volume with overresection of the bladder neck. Over-resection of the bladder neck can lead to brosis or scarring of the bladder neck, which in turn leads to BNC.…”
Section: Discussionmentioning
confidence: 99%
“…5 Many risk factors have been associated with BNC, such as untreated preoperative urinary tract infection, small prostate volume, unsuitable resectoscope diameter, long operative time, history of prostatitis and postoperative Foley insertion. [5][6][7] The aim of the current study was to investigate the preoperative parameters associated with the occurrence of BNC after TURP or ThuP, and the difference in BNC incidence rates between TURP and ThuP.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Therefore one should be more attentive when making indication of TURP for small-sized prostates. [25] The authors have indicated that bladder neck incision performed at the end of TURP may decrease the risk of development of bladder neck contracture. [26] In our study, when one considers that median volume of resected prostates was 29 cm 3 , then median incidence rate of contracture was 5.2% which is within an acceptable range.…”
Section: Discussionmentioning
confidence: 99%